Desulfurization reactant gas-solid coupled diffusion within CaO grain aggregate in the flue gas of coal-fired power plant. Issue 4 (16th February 2016) - Shang, J. Y.; Liu, Z. L.; Wang, S. L.; Wang, C. B.; Liu, H. C.
ABSTRACT: There is still room for further improvement in the SO2 removal efficiency of dry limestone desulfurization in the coal-fired power plant. The micro-structure of limestone particle is experimentally investigated by thermogravimetric analysis, scanning electron microscopy, and Mercury porosimeter. Gaseous diffusion theory and solid-state ion diffusion theory are coupled to derive dimensionless mass transfer equations, which are verified by thermogravimetric analysis in 3, 000 ppm SO2 . It is derived that solid-state ion diffusion controls the initial reaction stage. More attention should be paid to the fact that any pathway to improve solid-state ion diffusion velocity is useful for limestone desulfurization efficiency.